Peran Filsafat Pendidikan Islam dalam Membentuk Karakter Kemandirian Anak Asuh Panti Asuhan Putri IPHI Karanganyar - Tarno, Tarno; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study is motivated by the lack of independence among children in orphanages, despite independence being a fundamental skill essential for their future. The aim of the research is to explore the role of Islamic educational philosophy in shaping the character of independence among foster children at Panti Asuhan Yatim Putri IPHI Karanganyar. A qualitative approach with a descriptive method was employed, based on observations of foster children ranging from junior to senior high school age. The findings reveal that the level of independence among the children varies, influenced by parenting styles, social environment, and the educational system implemented at the orphanage. Some children still show dependence on caregivers, both in personal decision-making and in daily social life. For instance, when instructed to clean the table after meals, some children were reluctant to comply directly and tended to pass responsibility to others. This condition aligns with Suyanto’s (2009) findings, which state that orphanage children tend to be passive, lack initiative, and struggle to make independent decisions without guidance. Therefore, structured and continuous development rooted in Islamic educational philosophy based on the Qur’an and Hadith is necessary to instill the value of independence in foster children.